Characteristics of Nasopharyngeal Microbiocenosis and Evaluation of the Interaction of its Associates in Women with Chronic Endometritis - E. A. Kungurtseva; M. A. Darenskaya; E. I. Ivanova; А. А. Pristavka; T. V. Tunik; U. M. Nemchenko; E. V. Grigorova; O. Ya. Leshchenko (Acta Biomedica Scientifica, 2019)
The upper respiratory tract is one of the most important biotopes in the human body. Therefore, in order to understand the cause-effect relationships between the microbial world and the pathological state of a person, it is crucial to clarify the relationship of the microbes-associates.The study involved 74 women with reproductive disorders. The main group – women with chronic endometritis (n = 47). The diagnosis of chronic endometritis was revealed on the basis of morphological signs of histological examination of aspirates from the uterine cavity. The comparison group consisted of 27 women, in whom the chronic endometritis was not confirmed. When applying, women complained more often of infertility and (or) miscarriage. Of the accompanying extragenital diseases, chronic tonsillitis in women of the studied groups was most often diagnosed. Therefore, it was important to give a microbiological description of the nasopharyngeal biotope of these women, as one of the factors that influences the reserves of confrontation of the reproductive function of the body to infections. Nasopharyngeal microbiocenosis of women with chronic endometritis was characterized by deficiency of the indigenous microbiota and a permanent presence in the microbiocenosis of the absolute pathogen (S. aureus) and transient species (enterococci, CNS). Between the representatives of normoflora antagonistic relations were established. The obtained results indicate violations in the nasopharyngeal biotope of these women, which can cause immunodeficiency and, as a consequence, the development and flow of chronic endometritis.